Revolution Under Attack - Cohen, Ronen A. author. aut Link
XVIII, 186 p.
Keywords: During the revolution in Iran, a small, fanatical group called the Forqan used targeted assassinations of religious leaders to fight the Ayatollah Khomeini's plan to establish a theocratic Islamic state. Ronen A. Cohen examines what really happened behind the fog of revolution.